Tolerance in City Planning as a central element for understanding the transformation of the urban fabric of a historic city: Applying the Plan Cort in Valladolid under Franco’s dictatorship. - Sainz Guerra, José Luis; Sainz Esteban, Alicia; Del Caz Enjuto, Rosario (International Planning History Society Proceedings, 2024)
The Plan Cort was applied in the city of Valladolid during the first years of Franco’s dictatorship. This urban plan was characterized by the application of the classical rules of city planning at that time. It was a plan to reform the street alignments in the historic centre alongside the construction of working class suburbs on the outskirts and new-build areas beyond the city limits. Actions in the years that followed focused on reforming the historic centre, elevating the permitted heights and increasing the authorized buildable depths. By analysing the licenses of the time, we can conclude that a system of concessions for licenses had been established that openly breached the regulations of the Plan, violating numerous legal requirements. Perhaps the most important violations involved the permitted heights, which were frequently over the maximum authorized. The most important proposals were gradually diluted through a long series of reforms and modifications. It was those who approved the Plan who, in the end, transformed it until it was practically unrecognisable. The Plan was in fact a decoy, a false image of modernity behind which a distracted, self-interested administration hid. As a result of the said flexibility, in several streets of the city of Valladolid, it is currently possible to see the different scales, the typological rupture and the stark contrast between modern and traditional buildings side by side, which have given rise to an urban landscape with a great dissonance.